KIDNEY FUNCTION DECLINE AND MORTALITY IN DONORS WITH EXPANDED CRITERIA - FIVE YEARS FOLLOW UP STUDY - Trajcheska, Lada; Filipovski, Stefan; Nikolov, Igor; Severova, Galina; Sterjova, Zaklina; Karanfilovski, Vlatko; Sulejman, Sabir; Rambabova, Emilija; Canevska, Aleksandra; Rambabova Busletikj, Irena; Spasovski, Goce (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Kidney donors are considered healthy, but with a need for continued medical follow up and encouragement for continued healthy lifestyle, especially when expanded criteria for donation are applied.  This study aims to analyse the five years follow up of kidney donors after explanation, encountering risks of kidney function decline and donorsâ€™ mortality. In a retrospective study we evaluated a donor cohort with 5 years of follow up. Demographic characteristics as age, gender and the presence comorbidities as diabetes, hypertension, hyperlipidemia and Body Mass Index (BMI) >30kg/m 2 were analyzed. Estimated glomerular filtration rate (eGFR) by CKD EPI formula was notified prior donation, and annually afterwards. Consultations with nephrologist or other specialists were notified. In a multivariate regression analysis, the reduction ratio (RR) of eGFR was explored as dependent variable. Cox regression analysis exploited mortality; Kaplan Meier survival curve was applied in respect of BMI. Seventy-five donors with average age above 55 years were predominantly women (69%), nearly every nineth patient had diabetes or obesity (9%). Proportion of donors referred to nephrologist at the 12 months, declined up to 58% at the fifth year, ignoring medical checks showed ascending trend to 16% at the end of second and third year and 12% at the end of observational period.   The univariate regression analysis found diabetes, hyperlipidemia and hypertension, the presence of multiple comorbidities, gender and age as insignificant predictors of eGFR 12 months reduction ratio. The nephrologist referral showed borderline significance (Î² = - 0.103, p=0.076). Only BMI over 30kg/m 2 worsened the kidney function (Î² = 0.600, p=0.001). Five years mortality rate was 6.7%. The diseased donors were significantly older, more frequently had diabetes and obesity also they had significantly lower eGFR pre-donation, at the end of the first year but also and more step decline of it after 12 months. In the multivariate analysis BMI>30kg/m 2 emerged as most powerful predictor of mortality (HR 40.02; CI: [4.11-389), p=0.0001). Survival of obese patients was significantly shorter when compared with patients with lower body weight (43.28 Â± 7.51 vs. 59.33Â±0.65, Log rank p=0.000), respectively. Our study demonstrates that the mortality and declination of renal function after donation are associated with nephrologist referral and other potentially modifiable factors, especially obesity. Improved protocols for pre-donation information, education and adequate after-donation follow up is mandatory to achieve better longevity and kidney function survival in these frail and precious individuals.  Key words: donors, kidney function decline, mortality, obesity, nephrologist referral.